Deaf and non-deaf basketball and volleyball players' multi-faceted difference on repeated counter movement jump performances: Height, force and acceleration - Soslu, Recep; Özer, Ömer; Uysal, Abdullah; Pamuk, Ömer (Frontiers in Sports and Active Living, 2022)
The aim of this study was to compare the performances of Repetitive Counter Movement Jumping (basketball/volleyball) of deaf/non-deaf athletes. Athletes playing in the Turkish Deaf Basketball and Volleyball national teams and in Basketball and Volleyball First Leagues participated in the study. The study group consisted of 51 male athletes, including deaf basketball (n = 11; age: 26.18 ± 4.79 years), deaf volleyball (n = 12, age: 26.33 ± 4.27 years), non-deaf basketball (n = 14, age: 26.93 ± 4.87 years), and non-deaf volleyball (n = 14, age: 24.93 ± 5.10 years) players. As a result of the test, Jump Height from Take Off Velocity, Jump Height from Take Off Velocity, Jump Height from Flight Time, Counter Movement Acceleration, Push Off Acceleration, Average Velocity, Average Power, and Average Force were analyzed. Differences in the jump performances among the groups (deaf basketball and volleyball, non-deaf basketball, and volleyball) were tested by one-way analyses of variance (ANOVA) with Tukey's post-hoc follow-up testing when necessary for jump test. As a result, this is the first study to investigate the number of jumps and jump height, the force produced, acceleration at the time of jump, and jump velocity during 30 s in deaf and non-deaf basketball and volleyball players within the scope of individual Repeated Counter Movement Jump test. Based on the biomechanical changes according to our results, our findings show a greater decrease in the number of jumps and jump heights, the force produced, the acceleration at the moment of the jump and the jump velocity in all athletes, especially those that affect the deaf.